Pyrrolizidine alkaloids from seven wild-growing Senecio species in Serbia and Montenegro - BORIS M. MANDIC; DEJAN N. GODJEVAC; VLADIMIR P. BESKOSKI; MILENA R. SIMIC; SNEZANA S. TRIFUNOVIC; VELE V. TESEVIC; VLATKA V. VAJS; SLOBODAN M. MILOSAVLJEVIC (Journal of the Serbian Chemical Society, 2009)
The genus Senecio (family Asteraceae) is one of the largest in the world. It comprises about 1100 species which are the rich source of pyrrolizidine alkaloids. Plants containing pyrrolizidine alkaloids are among the most important sources of human and animal exposure to plant toxins and carcinogens. The pyrrolizidine alkaloids of seven Senecio species (S. erucifolius, S. othonnae, S. wagneri, S. subalpinus, S. carpathicus, S. paludosus and S. rupestris) were studied. Fourteen alkaloids were isolated and their structures determined from spectroscopic data (1H- and 13C-NMR, IR and MS). Five of them were identified in S. erucifolius, four in S. othonnae, two in S. wagneri, four in S. subalpinus, two in S. carpathicus, three in S. paludosus and three in S. rupestris. Seven pyrrolizidine alkaloids were found for the first time in particular species. The results have chemotaxonomic importance. The cytotoxic activity and antimicrobial activity of some alkaloids were also studied.